Fixed-time insemination of suckled beef cows. 1. select synch, cosynch, and their combination - Thompson, K. E.; Lamb, G.C.; Stevenson, Jeffrey S.; Grieger, David M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
As in our previous studies, the GnRH + PGF2" treatment was very effective in inducing a fertile estrus and(or) ovulation. Ovulations induced in response to the first GnRH injection averaged 48% in three herds and ranged from 44 to 56%. The proportion of 536 cows that were cycling at the beginning of the breeding season averaged 48% and ranged from 35 to 59%. Conception rate was greater in Select Synch cows (those inseminated after detected estrus) than in cows in other breeding treatments. Pregnancy rates tended to be greater in Select Synch cows than in cows of other treatments. A treatment × herd interaction indicated that alternate breeding treatments performed differently in each herd. These results also emphasize the importance of early cycling activity to reproductive outcomes.
Keywords: Beef; AI; Estrus-ovulation synchronization; GnRH; PGF2; Cows